Global Attractivity of a Family of Max-Type Difference Equations - Xiaofan Yang; Wanping Liu; Jiming Liu (Discrete Dynamics in Nature and Society)
We propose to study a generalized family of max-type difference equations and then prove the global attractivity of a particular case of it under some parameter conditions. Through some numerical results of other cases, we finally pose a generic conjecture.